INTERNALIZING THE VALUES OF RELIGIOUS MODERATION THROUGH PARSUBANG LOCAL WISDOM-BASED EDUCATION IN NORTH SUMATERA - Doli Witro; Luqyana Azmiya Putri; Vegia Oviensy (Harmoni, 2022)
This article reveals how to internalize the values ​​of religious moderation through education based on local wisdom Parsubang local wisdom in the province of North Sumatra. Parsubang is a term for a group or someone who attends or attends a wedding. In the Batak community in North Sumatra Province, Parsubang is understood as a group of relatives who are not allowed to eat pork because they are followers of the Islamic religion who attend a party. The party holding the party usually prepares food that uses the services of others to cook it, which incidentally is halal in the view of Islam. This article uses a qualitative research method with a grounded theory approach. Data analysis techniques are condensation, data presentation, and drawing conclusions. This article finds that the Parsubang tradition in the Batak community reflects four indicators of religious moderation formulated by the Ministry of Religion of the Republic of Indonesia, namely commitment to the nation, anti-violence against fellow citizens, tolerance for adherents of other religions, and accommodativeness to regional culture. These four things are reflected in the actions of Western society, which are mostly Catholics or Christians who invite and present Muslims to their wedding celebrations, and they also hire extraordinary cooks to be able to prepare food that is halal in the view of Islam and cooked in different places for can give confidence to Muslims who attend and eat the food served at a party.